Previous Crop Impacts Winter Wheat Sowing Dates, Available Water at Sowing, and Grain Yield - L. M. Simão; A. Patrignani; S. Cominelli; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2023)
Cropping systems choices can directly affect the sowing date for winter wheat, which is among the most important variables that determine attainable yields in the U.S. Central Great Plains. Our objective was to investigate the effect of the previous crop on winter wheat grain yield through the modulation of sowing date and its impact on plant available water at sowing, and temperatures during the critical period for yield determination. A no-tillage rainfed field experiment was established in 2019 at Ashland Bottoms, KS. Winter wheat was sown either after summer fallow, full-season soybean, double-cropped soybean, or corn—thus, resulting in a range in sowing dates of 270–326 days of the year (September 27 to November 22). The optimum sowing date for the site based on grain yield was estimated at day of year 296 ± 5 (October 18 to 28). Winter wheat after summer fallow and after a fullseason soybean crop resulted in the greatest yields, whether sown at the optimum date or slightly later than optimum. Winter wheat yield was positively related to plant available water at sowing. Later sowing dates were most likely to reduce plant available water at sowing, and could delay wheat’s development resulting in higher temperatures occurring during the critical period for yield determination (i.e., the days surrounding anthesis). Later sowing also shortened grain filling duration due to an overall later cycle and elevated temperatures. Thus, adjusting winter wheat sowing dates is the first step that determines the crop’s yield potential through improved plant available water at sowing, and reduced temperatures during the critical period for yield determination. When following a summer crop, winter wheat should be sown as soon as the previous crop is harvested to try to mitigate these negative effects of late sowing.
Keywords: wheat; planting date; heat stress; water use